Analysis of PSAK 16 Accounting Implementation at BAPPEDA of North Sumatra Province - Sri Eka Putri; Kamilah K (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This study plans to evaluate the extent to which the organization has made accounting arrangements for fixed assets according to the hypothesis, which depends on the Statement of Financial Accounting Standards (PSAK) No.16 in organizational activities in the Regional Development Planning Agency (BAPPEDA) of North Sumatra Province. This study is a descriptive qualitative type that describes data in the form of a narrative about objects found in the field. The results of this study can be concluded that in general accounting activities, especially in the management of fixed assets, BAPPEDA, North Sumatra Province, the principles are almost in accordance with the Statement of Financial Accounting Standards (PSAK) No. 16 in terms of recognition, measurement, disposal of assets, depreciation of property, plant and equipment, retirement and disposal of property, plant and equipment. However, as far as showing and describing fixed assets, there are some data that are not clearly disclosed in the notes to the budget report. The Company does not disclose the estimation premise used in determining the gross amount. What's more, it does not reveal the asset reduction strategy used